Inheritance, civil procedure, and justice: a critical analysis - Feibe Engeline Pijoh; Nanda Dwi Rizkia; Neni Hardiati; Rahmat Setiawan; Sahrul; Henny Saida Flora (Journal of Law Science, 2024)
This research will use the writings of two contemporary Islamic legal experts, Nasr Hamid Abu Zayd and Muhammad Syahrur, to delve into the idea of gender equity in Islamic inheritance and wills. This research uses a philosophical and analytical approach to clarify how the two thinkers reach a more egalitarian and gender-neutral understanding of religious texts concerning inheritance law. The analytical descriptive approaches are used to describe and investigate Islamic legal ideas and positive law enforcement mechanisms relevant to gender issues and inheritance. The research shows that both experts believe that ijtihad and adapting Islamic law to contemporary society are crucial to achieving gender equality and justice. There is mounting evidence, including this research, that Islamic inheritance law may need a reevaluation in view of advances in gender equality and other notions of inclusive social justice